Volume 7B: Structures and Dynamics 2016
DOI: 10.1115/gt2016-56593
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Inlet Distortion on the Flutter Stability of a Highly Loaded Transonic Fan Rotor

Abstract: The fundamental mechanisms of blade flutter in modern aircraft engines are very complex. Flutter is a self-excited aeroelastic instability phenomenon which can finally cause material fatigue and, in the worst case, leads to blade failure within a very short time. The risk of flutter has to be considered during the design process and it is necessary to avoid that safety risk. The aeroelastic stability has to be ensured over the whole operating range especially near operating limits or typical flutter boundaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The minimum damping occurs at ND = 0. This flutter stability behavior is consistent with that by Iseni (Iseni et al, 2016).…”
Section: Flutter Analysis Of the Nasa Rotor 67 With Clean Inletsupporting
confidence: 91%
See 2 more Smart Citations
“…The minimum damping occurs at ND = 0. This flutter stability behavior is consistent with that by Iseni (Iseni et al, 2016).…”
Section: Flutter Analysis Of the Nasa Rotor 67 With Clean Inletsupporting
confidence: 91%
“…8, the deformation of tip region indicates that the first two modes are bending modes and the third mode is a torsion mode. Both the natural frequencies and mode shapes are consistent with that by Iseni (Iseni et al, 2016).…”
Section: Modal Analysis Of the Nasa Rotor 67supporting
confidence: 86%
See 1 more Smart Citation
“…This suggests that separation is the primary driver of blade flutter, while the shock wave enhances the aeroelastic stability of the blades. Similar findings were reported in studies by Iseni [12] and Purushothaman et al [13]. However, these conflicting conclusions were highlighted by Dong [14], who Aerospace 2024, 11, 358 2 of 17 indicated that the difference in the stabilizing or destabilizing effects of shock wave and flow separation is related to changes in the blade throat area, with the influencing mechanisms remaining unclear.…”
Section: Introductionmentioning
confidence: 51%